2020
DOI: 10.1007/s11218-020-09554-2
|View full text |Cite
|
Sign up to set email alerts
|

Who sees the most? Differences in students’ and educational research experts’ first impressions of classroom instruction

Abstract: In recent decades, the assessment of instructional quality has grown into a popular and well-funded arm of educational research. The present study contributes to this field by exploring first impressions of untrained raters as an innovative approach of assessment. We apply the thin slice procedure to obtain ratings of instructional quality along the dimensions of cognitive activation, classroom management, and constructive support based on only 30 s of classroom observations. Ratings were compared to the longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 70 publications
3
16
0
1
Order By: Relevance
“…These outcomes are in line with Carter's et al (1988) original results and support their interpretation that highly developed memory structures of in-service teachers facilitated their reasoning processes-particularly in explaining classroom phenomena-relative to pre-service teachers in the very beginning of their teaching careers. As such, the study findings contribute to previous research evidence on the superiority of knowledge-based reasoning in experienced teachers compared with student teachers (Schäfer and Seidel, 2015;Meschede et al, 2017;Wolff et al, 2017;Kim and Klassen, 2018;Krepf et al, 2018;Yang et al, 2019;Gegenfurtner, 2020) and add to the broader literature on professional expertise (Damşa et al, 2017;Craig, 2019;Neumann et al, 2019;Szulewski et al, 2019b;Backfisch et al, 2020;Begrich et al, 2020;Boshuizen et al, 2020). Hypotheses 1b and 1c are thus supported.…”
Section: Principal Findingssupporting
confidence: 80%
“…These outcomes are in line with Carter's et al (1988) original results and support their interpretation that highly developed memory structures of in-service teachers facilitated their reasoning processes-particularly in explaining classroom phenomena-relative to pre-service teachers in the very beginning of their teaching careers. As such, the study findings contribute to previous research evidence on the superiority of knowledge-based reasoning in experienced teachers compared with student teachers (Schäfer and Seidel, 2015;Meschede et al, 2017;Wolff et al, 2017;Kim and Klassen, 2018;Krepf et al, 2018;Yang et al, 2019;Gegenfurtner, 2020) and add to the broader literature on professional expertise (Damşa et al, 2017;Craig, 2019;Neumann et al, 2019;Szulewski et al, 2019b;Backfisch et al, 2020;Begrich et al, 2020;Boshuizen et al, 2020). Hypotheses 1b and 1c are thus supported.…”
Section: Principal Findingssupporting
confidence: 80%
“…In addition to substantiating previous findings, we contribute evidence that the child's perspective can yield meaningful insights into drivers of teacher quality variation (see, e.g., Begrich et al 2020. In many regards, our approach may be more advantageous than the classroom observation approach (cf.…”
Section: Introductionsupporting
confidence: 80%
“…Lastly, multiple measures from different perspectives are necessary when studying teacher quality. As and others (e.g., Begrich et al 2020) describe, various assessments can serve as tools for targeting teachers, supporting development, measuring and evaluating progress, and helping policymakers improve quality.…”
Section: Introductionmentioning
confidence: 99%
“…The related research has shown differences between experienced teachers and preservice teachers in their noticing and knowledgebased reasoning (Schäfer, 2014;Seidel et al, 2020). The results indicate that expert and novice teachers differ relatively little with regard to general noticing skills (Begrich et al, 2020). However, experts outperform novices with regard to their knowledge-based reasoning skills.…”
Section: Teacher Professional Visionmentioning
confidence: 94%